Topical nitroglycerin in newborns with ischemic injuries: A systematic review - Rafat Mosalli; Wed Khayyat; Sarah Al Qarni; Amirah Al Matrafi; Mohamed El Baz; Bosco Paes (Elsevier, 2021)
Background: Arterial catheterization is frequently performed in neonatal intensive care units with an inherent risk of peripheral ischemic injury, especially in preterm infants. The treatment options following vascular damage involve invasive and non-invasive modalities. The primary objective of this systematic review was to evaluate the evidence of the use of topical nitroglycerine (TNG) either alone or as adjunctive therapy. The secondary aim was to develop an approach to the treatment of catheter induced ischemia in infants based on the available evidence. Methods: A comprehensive search was conducted of available databases for relevant articles that involved the treatment of peripheral tissue ischemia in neonates with the use of TNG. Citations were restricted to human subjects. Results: Six hundred and eighty-nine articles were identified, and twenty-seven case reports and case series were compatible with the inclusion and exclusion criteria. Sixty-eight infants out of the 76 published cases (89%) experienced a favorable outcome and 79% (n = 60) demonstrated complete recovery with the topical application of TNG to the ischemic site. Conclusion: The available evidence demonstrates that TNG is effective for the treatment of peripheral ischemia in neonates after standard conservative measures have failed. However, due to the absence of robust evidence for this therapeutic modality, there are no uniform guidelines regarding the frequency, duration, and safety of TNG use. Planning the management of peripheral ischemia in neonates with TNG should be a multidisciplinary decision that includes close surveillance of blood pressure, methemoglobin levels, and follow up cranial ultrasound.